Spasmodic versus spasmolytic activities of Euphorbia spinidens extract on rat isolated uterus - Mustafa Ghanadian; Hassan Sadraei; Zeinab Cheraghi (Wolters Kluwer Medknow Publications, 2016)
Preterm contraction of uterus is a main cause of miscarriages and preterm labour. Euphorbia known as Ferphion in Iranian traditional medicine texts like Al-Hawi, is reported for prevention of preterm labour. Therefore, the objective of this research was to investigate the effect of Euphorbia spinidens Bornm. Ex Prokh. on motility of rat uterus. Uterine horns were isolated form non-pregnant female rats pretreated with estrogen. E. spinidens hydroalcoholic extract was examined on KCl (80 mM) induced and spontaneous periodic contraction in isolate uterine strips suspended in an organ bath and compared with nifedipine and ritodrine. In isolated rat uterine strips, E. spinidens extract (1-500 µg/mL) showed mixed effects. At lower concentrations, firstly potentiated the spontaneous periodic contraction, while in concentrations above 256 µg/mL the spontaneous periodic contractions were completely attenuated. These findings demonstrated that although lower concentrations of hydroalcoholic extract potentiated the spontaneous periodic contraction of rat uterine smooth muscle, but at higher concentrations it had inhibitory effect on rat uterus contraction.